Dampak Berkembangnya Waralaba Minimarket (Indomaret Dan Alfamart) Terhadap Pendapatan Pedagang Kecil Atau Toko Kelontong Di Kecamatan Banjarmasin Utara Kota Banjarmasin - Muhammad Rizky Novriady; N Nasrudin (PPJP Universitas Lambung Mangkurat, 2021)
This study aims to determine and analyze the impact of the establishment of a minimarket franchise on the income of small traders or grocery in North Banjarmasin sub-district. The data used are primary data and secondary data obtained through in-depth interviews based on questionnaires by researchers that have been prepared and observations of traders and buyers of grocery stores scattered in the city of Banjarmasin, northern Banjarmasin district. The analytical tool used is paired sample t-test. Furthermore, descriptive analysis is used to determine the impact of the existence of the minimarket franchise on grocery traders.Based on paired sample t-test, it was proven that the existence of the franchise had an impact on the grocery store merchants in the city of Banjarmasin, North Banjarmasin. This can be seen from the decline in income from before and after the existence of a minimarket franchise.